A Mini-Review of Flavone Isomers Apigenin and Genistein in Prostate Cancer Treatment - Ji, Xiaozhen; Liu, Kai; Li, Qingyue; Shen, Qun; Han, Fangxuan; Ye, Qingmei; Zheng, Caijuan (Frontiers in Pharmacology, 2022)
The initial responses to standard chemotherapies among prostate cancer (PCa) patients are usually significant, while most of them will finally develop drug resistance, rendering them with limited therapies. To discover new regimens for the treatment of PCa including resistant PCa, natural products, the richest source of bioactive compounds, can serve as a library for screening and identifying promising candidates, and flavones such as apigenin and genistein, have been used in lab and in clinical trials for treating PCa over decades. In this mini-review, we take an overlook into the progress of apigenin and genistein, which are isomers, in treating PCa in the past decade. While possessing very similar structure, these two isomers can both target the same signaling pathways; they also are found to work differently in PCa cells. Given that more combinations being developed and tested, genistein appears to be more promising to be approved. The anticancer efficacies of these two flavones can be confirmed by in-vitro and in-vivo studies, their applications remain to be validated in clinical trials. Information gained in this work may provide important information for the new drug development and the potential application of apigenin and genistein in treating PCa.